The Role of Technology in Islamic Education to Improve Students' Cognition at Madrasah Tsanawiyah - Muzaidin, Muhammad; Kustoro; Abidin, Zaenal (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Islamic education in the digital era requires innovation in learning methods to support the development of thinking skills of Madrasah Tsanawiyah students. Ideally, technology can be an effective tool to create an interactive learning environment and support the development of student cognition. However, the reality shows that the use of technology in Islamic education is still very limited. This limitation can be seen from the lack of technological infrastructure and the low competence of teachers in integrating technology into the learning process. The gap between expectations and reality is the basis for this study. The focus of the study is to explore the role of technology in Islamic education learning and its impact on improving student cognition. This study uses a qualitative approach with a literature study method. Data were obtained through literature studies, digital documentation, and selection of relevant sources. Data analysis was carried out thematically to identify patterns and relationships between technology and student cognitive development. The results of the study show that technology has an important role as a learning medium that facilitates the understanding of religious concepts and improves students' critical thinking skills and creativity. The discussion emphasizes the need for training for teachers to maximize the use of technology. In conclusion, technology has great potential in improving students' cognition if used optimally